2001
DOI: 10.1046/j.0028-646x.2001.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic variation in heavy metal accumulation in angiosperms

Abstract: The influence of phylogeny on shoot heavy metal content in plants was investigated and the hypothesis tested that traits impacting on the accumulation of cadmium, chromium, copper, nickel, lead and zinc in plant shoots are associated.• Data suitable for comparative analyses were generated from a literature survey, using a residual maximum likelihood (REML) procedure. Both pair-wise regressions and principal components analyses (PCA) were performed on independent contrasts of shoot metal content. • Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
3
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(147 citation statements)
references
References 67 publications
6
131
3
3
Order By: Relevance
“…Even so, for most plants its toxicological effects are still poorly described (Jordan et al, 2010;Street, Stirk, & Van Staden, 2008). Despite the secondary metabolites' toxicity (Sirikantaramas, Yamazaki, & Saito, 2008), other internal components can be toxic, as heavy metals often bio-accumulated by aromatic plants (Broadley et al, 2001;F.M. Ferreira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, for most plants its toxicological effects are still poorly described (Jordan et al, 2010;Street, Stirk, & Van Staden, 2008). Despite the secondary metabolites' toxicity (Sirikantaramas, Yamazaki, & Saito, 2008), other internal components can be toxic, as heavy metals often bio-accumulated by aromatic plants (Broadley et al, 2001;F.M. Ferreira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports of inter-species comparisons in Sr concentrations of any isotope were compiled with data we generated for 85 Sr using the Residual Maximum Likelihood (REML) procedure of Broadley et al ( , 2001Broadley et al ( , 2003Broadley et al ( , 2004. Nine publications were identified that reported, without the possibility of foliar contamination, a comparison of concentrations of a Sr isotope in green shoots in two or more plant species growing on the same substrate under identical conditions.…”
Section: Methodsmentioning
confidence: 99%
“…REML analysis was run on the statistical package Genstat for Windows 5th Ed. release 4.2 (VSN International, Oxford, UK) (Thompson and Welham, 2001) using the programme of Broadley et al ( , 2001Broadley et al ( , 2003Broadley et al ( , 2004. Defining blocks and treatments in this way accounts for the absolute differences in values arising from blocks (experimental conditions) to reveal mean relative values for the treatments (species).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Cd is toxic for most of the important crop plants at concentrations more than 5-10 μg Cd g -1 leaf dry weight except some of the Cd-hyperaccumulators which can tolerate Cd concentrations of 100 μg Cd g -1 leaf dry weight. [16][17][18] However, Cd is toxic to plants even at low concentration in the soils but its phytotoxicity varies with the concentration of Cd in the soil as well as with the plant species and cultivars. Some plant species or cultivars content, as well as reduced CA activity.…”
Section: Introductionmentioning
confidence: 99%